Effect Of Tax Planning, Audit Quality, And Capital Intensity On Company Value With Independent Commissioners As Moderation Variables - Aziz Ambara; Melinda Malau (Al-Makki Publisher, 2023)
This study aims to test tax planning, audit quality, and capital intensity against company value moderated by independent commissioners. The purposive sampling method was used as a method in collecting his research data and the multiple regression equation model was used as his statistical analysis tool with the application of SPSS 25. The sample in this study is 29 issuers on the Indonesia Stock Exchange, especially manufacturing sector companies whose financial statements have been published for 5 (five) years from 2017 to 2021. Based on the results of this study showing that tax planning negatively affects the value of the company, independent commissioners audit quality strengthens the relationship between audit quality and company value. The quality of audits and independent commissioners tax planning has an insignificant effect on the value of the company. In addition, capital intensity, and independent commissioner capital intensity have no effect on the value of the company.